A discourse analysis of the representation of nursing in the National Disability Insurance Scheme pricing guide and eligibility criteria. Issue 1 (February 2023) - Pracilio, Amy; Wilson, Nathan J.; Kersten, Michelle; Trollor, Julian N.; Cashin, Andrew
ABSTRACT: Background: The Australian National Disability Insurance Scheme (NDIS) is conceptually grounded in the social model of disability, which focuses on removing disabling structures of society to allow people with disabilities full participation and improved quality of life. The social model rests on a dichotomous relationship against a medical model and its focus on treating impairments, and incorrectly places nursing within this paradigm. Aim: To undertake a discourse analysis of nursing as represented in the NDIS pricing guide and eligibility criteria, and to understand how the profession is conceptualised and valued within the scheme. Methods: Informed by Lauclau and Mouffe's poststructuralist theory, a discourse analysis of the floating signifier of nursing against the dominant nodal point of the social model of disability was undertaken through a close reading of the NDIS pricing guide and eligibility criteria. Findings: The nursing scope of practice is confined to physical/medicalised supports for people with disabilities. Nursing is excluded from offering therapeutic and behaviour supports and is structured and fiscally valued differently to other professions. Discussion: Despite its base in holistic and person-centred care, due to its conceptualisation within the medical model, the full scope of nursing practice is restrictive within the NDIS. This misarticulation of nursing excludes key aspects of adaptive, therapeutic, and holistic practice which can improve health outcomes for people with disabilities. Conclusion: The NDIS in its conceptual construction based on the social model of disability has upheld a vision of nursing inconsistent with practice relevant to caring for people with disabilities.